Advances in robot design and intelligent control : proceedings of the 24th International Conference on Robotics in Alpe-Adria-Danube Region (RAAD) /: proceedings of the 24th International Conference on Robotics in Alpe-Adria-Danube Region (RAAD). ([2015]) - Unknown
No abstract available